Measurement Of Diffusion Coefficient Of Ethanol In Pure Water By Using Moiré Deflectometry Technique - Guyita Kussia (My University, 2017)
In this research work measurement of diffusion coefficient of two miscible liquids is reported. The liquids are various combinations of ethanol and pure water. Moiré Defelectometry method was used in order to measure the diffusion coefficient of ethanol solution in pure water at room temperature (23±2 0C). The apparatus were: He-Ne laser (λ= 632.8 nm), expanding and collimating lenses, the diffusion cell, two similar rhonchi gratings, thermometer, syringes, screen, CCD camera and computer, and they were carefully calibrated and adequate operating conditions were summarized. Measured with this apparatus, the average diffusion coefficient (D) of Ethanol solution in pure water, agree with those reported value in literature, which is D = (0.822 ± 0.02) X 10-9m2/s assuming that the diffusion process is one-dimensional. It is found that the diffusion coefficient of ethanol solutions increases linearly with increase in solute concentration.